IoT-BCR: A Blockchain and Cognitive Radio-Based Framework for Secure and Efficient Wireless Communication - Gomathi , M.; Manojkumar, D.; Rajeswari, P.; Ramaraj, S. (Journal of Neonatal Surgery, 2025)
Blockchain technology, cognitive radio systems, and the Internet of Things (IoT) combine to create a potentially exciting new way to improve communication security, dependability, and efficiency in the quickly changing field of wireless communication. This work presents a novel solution to handle the issues of data integrity and spectrum scarcity in Internet of Things environments. It is called the "IoT-based Blockchain and Cognitive Radio (IoT-BCR)" project, and it combines these technologies. In order to minimize computing overhead and enable dynamic spectrum access, the IoT-BCR project uses lightweight algorithms for cognitive radio decision-making. Enhancing data integrity and reliability is possible by utilizing blockchain technology, which guarantees the safe and unchangeable documentation of device interactions. Better communication performance and robustness were shown by a prototype system that was created and tested in a smart city setting. By advancing safe and robust IoT ecosystems, our research opens the door to more intelligent and connected urban settings